Contemporary topics 3 academic listening and note-taking skills - Beglar, David; Murray, Neil.; Rost, Michael ([S.l.] : Pearson Longman, 2009)
Features college lectures from several academic disciplines, including astronomy, political science, and biology.
Compact discs.
Advanced English.
Keywords: Note-taking.; English language -- Spoken English -- Problems, exercises, etc